Tailoring the diameter and density of self-catalyzed GaAs nanowires on silicon. (17th February 2015) - Matteini, Federico; Dubrovskii, Vladimir G; Rüffer, Daniel; Tütüncüoğlu, Gözde; Fontana, Yannik; Morral, Anna Fontcuberta I
Abstract: Nanowire diameter has a dramatic effect on the absorption cross-section in the optical domain. The maximum absorption is reached for ideal nanowire morphology within a solar cell device. As a consequence, understanding how to tailor the nanowire diameter and density is extremely important for high-efficient nanowire-based solar cells. In this work, we investigate mastering the diameter and density of self-catalyzed GaAs nanowires on Si(111) substrates by growth conditions using the self-assembly of Ga droplets. We introduce a new paradigm of the characteristic nucleation time controlled by group III flux and temperature that determine diameter and length distributions of GaAs nanowires. This insight into the growth mechanism is then used to grow nanowire forests with a completely tailored diameter-density distribution. We also show how the reflectivity of nanowire arrays can be minimized in this way. In general, this work opens new possibilities for the cost-effective and controlled fabrication of the ensembles of self-catalyzed III–V nanowires for different applications, in particular in next-generation photovoltaic devices.